Benefit of standard versus low-dose tirofiban for percutaneous coronary intervention in very elderly patients with high-risk acute coronary syndrome - Lin Yun-ling; Chen Liang-long; Luo Yu-kun; Zheng Xing-chun; Li Wei-wei (Acta Pharmacologica Sinica, 2016)
Aim: This study aimed to compare the efficacy and safety between standard and low-dose tirofiban in the treatment of elderly high-risk non-ST-segment elevation acute coronary syndrome (NSTE-ACS) patients who underwent percutaneous coronary intervention (PCI). Methods: Ninety-four very elderly (≥80 years) high-risk patients with NSTE-ACS were randomly assigned to the standard or the low-dose group. Upstream tirofiban was administered intravenously with a bolus dose of 0.4 μg·kg−1·min−1 over a period of 30 min after the diagnosis had been confirmed, and was followed by a 36−48 h infusion of 0.10 μg·kg−1·min−1or 0.075 μg·kg−1·min−1. PCI was performed within 24 h of admission. Platelet aggregation inhibition and thrombolysis in myocardial infarction (TIMI) grade flow were assessed. The major adverse cardiac events (MACEs), including death, myocardial infarction, recurrent angina and urgent target-vessel revascularization (TVR), were documented at 7 d, 30 d, and 6 months, and bleeding events were recorded at 7 d. Results: Although a significantly higher inhibition of platelet aggregation was observed in the standard-dose group (P0.05). The rate of MACEs was not significantly different at 7 days (2.1% vs 4.4%, P=0.61), 30 days (6.3% vs 8.7%, P=0.71) and 6 months (14.6% vs 17.4%, P=0.71). Major bleeding events were significantly higher in the standard-dose group (10.4% vs 0.0%, P=0.03). Conclusion: In very elderly high-risk patients with NSTE-ACS undergoing PCI, low-dose tirofiban offered about the same level of protection from major ischemic events that standard doses did, with less associated bleeding.